Growth, Yield and Grain Quality of Cowpea (Vigna unguiculata (L.) Walp.) and Weed Flora as Affected by Physical and Chemical Methods of Weed Control - Asare Osei Dennis; Kwadwo Gyasi Santo; Abdul Aziz Khalid; Kwabena Atakora; Daniel Afreh Ntiamoah; Muntala Abdulai; Adjei Eric (Legume Science)
ABSTRACT This study sought to identify the most effective weed control methods for enhancing growth, yield and grain quality in cowpea and to reduce weed interference during the major and minor rainy seasons of 2022 at Juaso in the Asante Akim South Municipality, Ghana. Sun‐zema at 30 mL/15 L of water, Supremo (90 mL/15 L of water), Vezir (90 mL/15 L of water), Ogyama (100 mL/15 L of water) and Benfop (100 mL/15 L of water), hoeing, cutlass weeding and no weeding were evaluated in a randomized complete block design with three replicates. Data on weed flora, plant height, number of leaves per plant, days to 50% flowering and pod formation, grain yield and yield components and proximate composition of cowpea grains were collected and subjected to analysis of variance using GenStat statistical package (11th edition). Differences in means were compared using the Fisher's protected least significant difference at a probability level of 5%. Significant (p < 0.05) improvements in the growth of cowpea due to hoe weeding were observed. Hoeing, Vezir and Supremo herbicides increased grain yield during the major rainy season, with hoeing recording the highest value (0.53 ± 0.07 ton/ha), whereas Supremo herbicide recorded the highest grain yield (0.38 ± 0.06 ton/ha) during the minor season. Hoeing recorded the least grain moisture contents of 7.45 ± 0.62% and 6.35 ± 0.62% in the major and minor seasons, respectively, which could enhance postharvest handling. Application of Supremo, Sun‐zema and Ogyama reduced weed diversity in the study area. The study recommends hoeing during the major season and herbicide application (Supremo) during the minor season.